Human Metapneumovirus (hMPV): Tantangan Baru dalam Kesehatan Global - Khairani, Rita (Fakultas Kedokteran Universitas Trisakti, 2025)
Human metapneumovirus (hMPV) is a respiratory virus belonging to the Pneumoviridae family, first identified in 2001. hMPV is closely related to respiratory syncytial virus (RSV), causing upper and lower respiratory tract infections that primarily affect vulnerable populations, such as children, the elderly, and individuals with weakened immune systems. It often circulates seasonally during winter and early spring. The incidence of hMPV is highest in young children. It is responsible for 5-10% of acute respiratory infections in hospitalized children and causes a crude mortality rate of 9%, similar to influenza A. Symptoms of hMPV infection vary from mild upper respiratory tract infections to bronchiolitis, bronchitis, and pneumonia. Nasal congestion and runny nose, cough, sore throat, and fever are common symptoms of this infection. Wheezing is common in children and requires the use of bronchodilators. Most hMPV patients recover within 7-10 days without complications. Some groups are at high risk for severe complications such as pneumonia and multi-organ failure requiring intensive care. Currently, laboratory diagnosis of hMPV infection is done by detecting viral nucleic acid in respiratory tract specimens. Serological tests using Immunofluorescence or ELISA (Enzyme-Linked Immunosorbent Assay) can be used to detect hMPV-specific antibodies, which are helpful in retrospective diagnosis and epidemiological studies. Rapid antigen tests, although practical, can vary in sensitivity and specificity. There is currently no specific treatment, and vaccination is still in the development stage, although significant progress has been made. Prevention remains the most important aspect in reducing the impact of hMPV, focusing on infection control to limit the spread of the virus, especially in vulnerable populations.